The information content of qualitative survey data - Müller, Christian (OECD Publishing, 2009)
The information content of qualitative survey responses are confronted with the corresponding quantitative figures on a firm-by-firm basis. This comparison permits to directly check the information content of the qualitative data. The findings indicate that survey respondents provide correct information, by and large. The results lend support to the Carlson-Parkin method and may pave the way towards improving variance estimates within this method
Keywords: Economics